Associated factors with delayed door to balloon time in STEMI patients - Bijan zamani; Sa’id Ghadimi; Maryam Chenaghlou; Ahmad Separham; Zahra Amirajam; Malek Abazari; Mohsen Abbasnezhad; Negin Zamani (International Journal of Cardiovascular Practice)
Introduction: The time interval from hospital arrival to the balloon inflation of catheter in coronary arteries is defined as Door to Balloon Time (DBT). Door to balloon time is a marker of primary Percutaneous Coronary Intervention (PCI) timeliness. Door to balloon time duration, associated factors and it’s relation to outcomes are not similar in various centers. Herein we aimed to define these issues in our region. Methods: In this study, 188 patients with ST Elevation Myocardial infarction (STEMI) diagnosis eligible for primary PCI were included. Demographic, clinical and time intervals from arrival in hospital to catheterization data of patients were recorded. Patients were followed for six-month in terms of mortality and admission. Results: After excluding patients with missed data, 174 patients were entered in the study. Mean age of patients were 60.8±11.81 years and 78% of patients were male. Median DBT was 70 minutes (IQR 25-75: 55-97 minute). One hundred and twenty three patients (71%) had timely door to balloon time. Patients with delayed door to balloon time had lower age, lower prevalence of typical chest pain and higher prevalence of PCI on Left Circumflex Artery (LCX) than timely group but these differences were not significant. (p values were 0.068, 0.074 and 0.070 respectively). Delayed DBT was evident in three segments of door to ECG, ECG to code and code to cath times (p values were, < 0.0001, 0.009 and < 0.0001 respectively) but the cath to balloon time was not significantly different between two groups (p value: 0.159). Although in-hospital mortality was higher in delayed group than timely group but the difference was not meaningful. (11.7% vs 4.9%, p value: 0.103) Six-month mortality and admission rate were not different between two groups. Conclusion: Door to balloon time was acceptable in this study and was comparable to developed countries. Albeit there is room for improvement due to modifiable delayed parts.